Carbon fiber reinforced PA6 composite material for 3D printing and preparation method thereof
By modifying the carbon fiber surface and melting and kneading with PA6 and SEBS, the problem of insufficient tensile strength and interlayer bonding strength in 3D printed parts in the prior art is solved, and the problem of insufficient tensile strength and interlayer bonding strength in 3D printed parts is realized. The effect of strength and bonding strength between high layers.
Patent Information
- Application Number
- CN202411746655.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing carbon fiber reinforced PA6 composite materials have increased impact strength but decreased tensile strength in 3D printed parts, and the interlayer bonding strength has not been effectively improved, making it difficult to meet the needs of strong and tough integration and high interlayer bonding strength.
Carbon fiber reinforced PA6 composite materials suitable for thermoplastics are prepared by modifying the carbon fiber surface, including deslurry, alkali treatment, silane treatment, maleic anhydride grafting and resizing, combined with PA6 and SEBS for melt-kneading.
The tensile strength, impact strength and interlayer bonding strength of carbon fiber reinforced PA6 composite material have been significantly improved, achieving 3D printed parts molding with strong and high interlayer bonding strength.
Smart Images

Figure CN119220090A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of additive manufacturing and polymer materials, and in particular to a carbon fiber reinforced PA6 composite material for 3D printing and a preparation method thereof. Background Art
[0002] Fused deposition modeling (FDM) is a commonly used 3D printing process with the advantages of low cost, simple operation and maintenance, high user penetration rate and wide material applicability. At present, commonly used FDM 3D printing materials include polylactic acid, acrylonitrile-butadiene-styrene copolymer, thermoplastic polyurethane, polyamide 6 (PA6), polyphenylene sulfide (PPS) and polyetheretherketone (PEEK). Therefore, the FDM process is favored in cultural and creative industries, personalized medical protective gear, personalized consumer products, new energy vehicles, aerospace and other fields.
[0003] PA6 has excellent mechanical properties and good wear resistance and corrosion resistance, and is a widely used engineering plastic. The mechanical strength of PA6 can be greatly improved after being reinforced with carbon fiber, further broadening its application field and is expected to become an important engineering plastic to replace metals such as steel and iron. The combination of carbon fiber reinforced PA6 composite materials and FDM technology will make the low-cost and efficient production of complex-shaped high-performance engineering parts a reality.
[0004] By mixing in polyolefin elastomers, the impact strength of carbon fiber reinforced PA6 composite 3D printed parts can be greatly improved to 21 kJ / m2, but its tensile strength is reduced to 94.1 MPa (Polymer Composites 2024;1–15.doi:10.1002 / pc.28783). This is mainly due to the weak interface bonding between carbon fiber and PA6 matrix. In addition, the above research work did not mention the interlayer bonding of 3D printed parts (z-direction tensile strength), which is particularly important for the service performance of 3D printed parts.
[0005] The carbon fiber currently on the market is mainly used to strengthen thermosetting plastics, using low molecular weight epoxy resin as the surface sizing agent. The affinity between the sizing agent and thermoplastics such as PA6 is weak, so it is difficult to form a strong interface effect during compounding, and its reinforcing effect cannot be fully exerted. Therefore, it is urgent to develop a carbon fiber surface modification method suitable for thermoplastics such as PA6 and the corresponding carbon fiber reinforced PA6 composite material, so as to be used for 3D printing of strong and tough, high-inter-layer bonding strength PA6 parts. Summary of the invention
[0006] In order to overcome the deficiencies of the prior art, an object of the present invention is to provide a carbon fiber reinforced PA6 composite material for 3D printing and a preparation method thereof.
[0007] To achieve the above object, the present invention provides the following solutions:
[0008] The present invention provides a carbon fiber reinforced PA6 composite material for 3D printing, comprising: the composite material is composed of the following components in percentage by weight;
[0009] PA6: 50wt%-95wt%;
[0010] Carbon fiber: 1wt%-45wt%;
[0011] SEBS: 3wt%-30wt%.
[0012] Preferably, the SEBS is at least one of unmodified SEBS and SEBS-g-MAH.
[0013] The present invention also provides a method for preparing a carbon fiber reinforced PA6 composite material for 3D printing, comprising:
[0014] Modify the surface of carbon fiber;
[0015] The modified carbon fiber tow is pulled into a twin-screw extruder for melt mixing and granulation with PA6 and SEBS to obtain a carbon fiber reinforced PA6 composite material.
[0016] Preferably, based on the carbon fiber reinforced PA6 composite material for 3D printing, the surface of the carbon fiber is modified, specifically:
[0017] Desizing the carbon fiber tow;
[0018] alkaline treating the desized carbon fiber tow;
[0019] treating the desized carbon fiber tow after the alkali treatment with silane;
[0020] Grafting maleic anhydride onto a silane-treated desized carbon fiber tow;
[0021] The grafted desized carbon fiber tow is re-sized.
[0022] Preferably, the carbon fiber tow is desizing treated, specifically by:
[0023] The desizing is completed by pulling the carbon fiber tow through a high temperature furnace, wherein the temperature is 200-400°C and the time of passing through the high temperature furnace is 0.5-3 minutes.
[0024] Preferably, the desized carbon fiber tow is subjected to an alkali treatment, specifically:
[0025] The desized carbon fiber tow is driven by traction to pass through a sodium hydroxide aqueous solution, wherein the concentration of the sodium hydroxide aqueous solution is 10 mol / L, and the passing time is 0.5-3 minutes. After passing through, the tow enters a clean water tank for cleaning.
[0026] Preferably, the desized carbon fiber tow after alkali treatment is subjected to silane treatment, specifically:
[0027] The cleaned desized carbon fiber tow is driven by traction to pass through a silane solution, wherein the silane is at least one of trimethoxysilane and triethoxysilane, the solvent of the silane solution is a mixture of water and ethanol or methanol, the volume ratio of water / ethanol or methanol is 90 / 10-20 / 80, the silane content in the silane solution is 0.5 wt%-20wt%, and the time for passing through the silane solution is 5-30 minutes.
[0028] Preferably, the desized carbon fiber tow treated with silane is grafted with maleic anhydride, specifically:
[0029] The desized carbon fiber tow treated with silane is driven by pulling through an aqueous maleic anhydride solution, wherein the maleic anhydride content is 1 wt%-30 wt%, the Custer catalyst content in the aqueous maleic anhydride solution is 0.1 wt%, the temperature of the aqueous maleic anhydride solution is 40-80°C, and the time of passing through the aqueous maleic anhydride solution is 5-30 minutes.
[0030] Preferably, the grafted desized carbon fiber tow is re-sized, specifically:
[0031] The grafted desized carbon fiber tow is driven by traction and dried in a blast high-temperature furnace, wherein the temperature is 120-180°C and the passing time is 2 minutes. The dried desized carbon fiber filaments are impregnated in a low molecular weight PA6 melt, wherein the PA6 molecular weight is 1000-11000 g / mol, the low molecular weight PA6 melt temperature is 220-260°C, and the passing time is 1-5 minutes, thereby completing the re-sizing.
[0032] Preferably, the modified carbon fiber tow is pulled into a twin-screw extruder for melt mixing and granulation with PA6 and SEBS to obtain a carbon fiber reinforced PA6 composite material, specifically:
[0033] The re-sized carbon fiber tow is pulled into a twin-screw extruder for melt mixing and granulation with PA6 and SEBS to obtain a carbon fiber reinforced PA6 composite material, wherein the molecular weight of PA6 is 12000-57000 g / mol and the extrusion mixing temperature is 220-270 °C.
[0034] According to the specific embodiments provided by the present invention, the present invention discloses the following technical effects:
[0035] The present invention provides a carbon fiber reinforced PA6 composite material for 3D printing and a preparation method thereof, the method comprising modifying the surface of the carbon fiber, pulling the modified carbon fiber tow into a twin-screw extruder for melt mixing and granulation with PA6 and SEBS to obtain a carbon fiber reinforced PA6 composite material. The present invention has the prospect of continuous production and is expected to provide a technical reference for customized sizing treatment of carbon fiber for the reinforcement of thermoplastics; the carbon fiber reinforced PA6 composite material and the preparation method thereof provided by the present invention are expected to become a demonstration of the technology promotion and application of producing strong and tough integrated engineering plastics and further 3D printing high-level inter-bonding strength engineering parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0037] Figure 1 A schematic diagram of a process for preparing a carbon fiber reinforced PA6 composite material for 3D printing provided in an embodiment of the present invention;
[0038] Figure 2 The SEM micrographs of the brittle fracture surfaces of the carbon fiber reinforced PA6 composite materials in Example 2 and Comparative Example 2;
[0039] Figure 3 Schematic diagram of DSC curves of the carbon fiber reinforced PA6 composite materials in Example 4, Comparative Example 4, Example 5 and Comparative Example 5. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] The purpose of the present invention is to provide a carbon fiber reinforced PA6 composite material for 3D printing. The prepared composite material can be 3D printed by FDM process. The parts printed by the carbon fiber reinforced PA6 composite material prepared by the present invention have the advantages of strong and tough integration and high bonding strength between high layers.
[0042] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0043] The present invention provides a carbon fiber reinforced PA6 composite material for 3D printing, wherein the composite material is composed of the following components in percentage by weight:
[0044] PA6: 50wt%-95wt%;
[0045] Carbon fiber: 1wt%-45wt%;
[0046] SEBS: 3wt%-30wt%.
[0047] The SEBS is at least one of unmodified SEBS and SEBS-g-MAH (maleic anhydride grafted SEBS).
[0048] Figure 1 A flow chart of a method provided by an embodiment of the present invention, such as Figure 1 As shown, the present invention also provides a method for preparing a carbon fiber reinforced PA6 composite material for 3D printing, comprising:
[0049] Step 100: modifying the surface of the carbon fiber;
[0050] Step 200: The modified carbon fiber tow is pulled into a twin-screw extruder to be melt-mixed with PA6 and SEBS and granulated to obtain a carbon fiber reinforced PA6 composite material.
[0051] In step 100, based on the carbon fiber reinforced PA6 composite material for 3D printing, the surface of the carbon fiber is modified, specifically:
[0052] Step 101: Desizing the carbon fiber tow;
[0053] Step 102: performing alkali treatment on the desized carbon fiber tow;
[0054] Step 103: performing silane treatment on the desized carbon fiber tow after the alkali treatment;
[0055] Step 104: Grafting maleic anhydride onto the desized carbon fiber tow treated with silane;
[0056] Step 105: re-sizing the grafted desized carbon fiber tow.
[0057] In step 101, the carbon fiber tow is desizing treated, specifically:
[0058] The desizing is completed by pulling the carbon fiber tow through a high temperature furnace, wherein the temperature is 200-400°C, preferably 300-360°C, and the time of passing through the high temperature furnace is 0.5-3 minutes, preferably 1-2 minutes.
[0059] In step 102, the desized carbon fiber tow is subjected to an alkali treatment, specifically:
[0060] The desized carbon fiber tow is driven by traction to pass through a sodium hydroxide aqueous solution, wherein the concentration of the sodium hydroxide aqueous solution is 10 mol / L, the passing time is 0.5-3 minutes, preferably 1-2 minutes, and then enters a clean water tank for cleaning.
[0061] In step 103, the desized carbon fiber tow after alkali treatment is subjected to silane treatment, specifically:
[0062] The cleaned desized carbon fiber tow is driven by traction to pass through a silane solution, wherein the silane is at least one of trimethoxysilane and triethoxysilane, the solvent of the silane solution is a mixed solution including water and ethanol or methanol, the volume ratio of water / ethanol (methanol) is 90 / 10-20 / 80, preferably 30 / 70-60 / 40, the silane content in the silane solution is 0.5 wt%-20 wt%, preferably 5 wt%-10 wt%, and the time for passing through the silane solution is 5-30 minutes, preferably 15 minutes.
[0063] In step 104, the desized carbon fiber tow treated with silane is grafted with maleic anhydride, specifically:
[0064] The maleic anhydride grafting reaction on the surface of the carbon fiber tow is that maleic anhydride reacts with silane on the surface of the carbon fiber tow to form a silane-hydrogen reaction and is grafted on the surface thereof, and the desized carbon fiber tow treated with silane is driven by traction to pass through an aqueous maleic anhydride solution, wherein the maleic anhydride content is 1 wt%-30 wt%, preferably 10 wt%, and the silane-hydrogen reaction is initiated by a Custer catalyst dispersed in the aqueous maleic anhydride solution, the Custer catalyst content in the aqueous maleic anhydride solution is 0.1 wt%, the temperature of the aqueous maleic anhydride solution is 40-80°C, preferably 55°C, and the time of passing through the aqueous maleic anhydride solution is 5-30 minutes, preferably 15 minutes.
[0065] In step 105, the grafted desized carbon fiber tow is re-sized, specifically:
[0066] The grafted desized carbon fiber tow is driven by traction to be dried in a blast high temperature furnace, wherein the temperature is 120-180°C and the passing time is 2 minutes. The dried desized carbon fiber filaments are impregnated in a low molecular weight PA6 melt, wherein the PA6 molecular weight is 1000-11000 g / mol, preferably 8000 g / mol, the low molecular weight PA6 melt temperature is 220-260°C, preferably 240°C, and the passing time is 1-5 minutes, preferably 2 minutes. In the low molecular weight PA6 melt, the maleic anhydride grafted on the surface of the carbon fiber tow reacts with the amino group on the PA6 molecular chain, thereby generating a covalent bond between the molecular chains, and re-sizing is completed by winding.
[0067] In step 200, the modified carbon fiber tow is pulled into a twin-screw extruder to be melt-mixed with PA6 and SEBS and granulated to obtain a carbon fiber reinforced PA6 composite material, specifically:
[0068] The re-sized carbon fiber tow is pulled into a twin-screw extruder for melt mixing and granulation with PA6 and SEBS to obtain a carbon fiber reinforced PA6 composite material, wherein the molecular weight of PA6 is 12000-57000 g / mol, the extrusion mixing temperature is 220-270°C, preferably 240-255°C, and the basic formula of the carbon fiber reinforced PA6 composite material prepared by extrusion is: PA6 accounts for 50-95 wt%, carbon fiber accounts for 1-45 wt%, and SEBS accounts for 3-30 wt%; the SEBS is at least one of unmodified SEBS or maleic anhydride grafted SEBS (SEBS-g-MAH);
[0069] The carbon fiber reinforced PA6 composite material prepared by extrusion mixing can be further prepared into wires with standard diameter (1.75 or 2.80 mm) for 3D printing, or directly printed using a pellet extrusion 3D printer.
[0070] The present invention provides six embodiments, and the carbon fiber reinforced PA6 composite material is prepared according to the above method, wherein the carbon fiber reinforced PA6 composite material is 3D printed by FDM process, and the mechanical properties of the product, especially the interlayer bonding strength, are tested and analyzed. The six embodiments are introduced respectively:
[0071] Embodiment 1:
[0072] 1. The re-sized carbon fiber tow was pulled into a twin-screw extruder, melt-mixed with PA6 and SEBS-g-MAH, and granulated to obtain a carbon fiber reinforced PA6 composite material, in which the carbon fiber content was 10 wt%, the PA6 content was 70 wt%, and the SEBS-g-MAH content was 20 wt%. The crystallization temperature of the composite material was tested by differential scanning calorimetry (DSC).
[0073] 2. The carbon fiber reinforced PA6 composite material was printed into a standard mechanical spline using the FDM process. The nozzle size was 0.4 mm, the nozzle temperature was 240 °C, the printing speed was 60 mm / s, and the printing direction was the x-axis direction; the standard mechanical spline used to evaluate the interlayer bonding strength was printed in the z-axis direction. The tensile strength of the spline was tested using an electronic tensile machine, and the notched impact strength of the spline was tested using an impact tester.
[0074] Embodiment 2:
[0075] 1. The re-sized carbon fiber tow was pulled into a twin-screw extruder, melt-mixed with PA6 and SEBS-g-MAH, and granulated to obtain a carbon fiber reinforced PA6 composite material, wherein the carbon fiber content was 20 wt%, the PA6 content was 60 wt%, and the SEBS-g-MAH content was 20 wt%. The crystallization temperature of the composite material was tested by differential scanning calorimetry (DSC).
[0076] 2. The carbon fiber reinforced PA6 composite material was printed into a standard mechanical spline using the FDM process. The nozzle size was 0.4 mm, the nozzle temperature was 240 °C, the printing speed was 60 mm / s, and the printing direction was the x-axis direction; the standard mechanical spline used to evaluate the interlayer bonding strength was printed in the z-axis direction. The tensile strength of the spline was tested using an electronic tensile machine, and the notched impact strength of the spline was tested using an impact tester.
[0077] Embodiment 3:
[0078] 1. The re-sized carbon fiber tow was pulled into a twin-screw extruder, melt-mixed with PA6 and SEBS-g-MAH, and granulated to obtain a carbon fiber reinforced PA6 composite material, in which the carbon fiber content was 30 wt%, the PA6 content was 50 wt%, and the SEBS-g-MAH content was 20 wt%. The crystallization temperature of the composite material was tested by differential scanning calorimetry (DSC).
[0079] 2. The carbon fiber reinforced PA6 composite material was printed into a standard mechanical spline using the FDM process. The nozzle size was 0.4 mm, the nozzle temperature was 240 °C, the printing speed was 60 mm / s, and the printing direction was the x-axis direction; the standard mechanical spline used to evaluate the interlayer bonding strength was printed in the z-axis direction. The tensile strength of the spline was tested using an electronic tensile machine, and the notched impact strength of the spline was tested using an impact tester.
[0080] Embodiment 4:
[0081] 1. The re-sized carbon fiber tow was pulled into a twin-screw extruder, melt-mixed with PA6 and SEBS-g-MAH, and granulated to obtain a carbon fiber reinforced PA6 composite material, in which the carbon fiber content was 20 wt%, the PA6 content was 75 wt%, and the SEBS-g-MAH content was 5 wt%. The crystallization temperature of the composite material was tested by differential scanning calorimetry (DSC).
[0082] 2. The carbon fiber reinforced PA6 composite material was printed into a standard mechanical spline using the FDM process. The nozzle size was 0.4 mm, the nozzle temperature was 240 °C, the printing speed was 60 mm / s, and the printing direction was the x-axis direction; the standard mechanical spline used to evaluate the interlayer bonding strength was printed in the z-axis direction. The tensile strength of the spline was tested using an electronic tensile machine, and the notched impact strength of the spline was tested using an impact tester.
[0083] Embodiment 5:
[0084] 1. The re-sized carbon fiber tow was pulled into a twin-screw extruder, melt-mixed with PA6 and SEBS-g-MAH, and granulated to obtain a carbon fiber reinforced PA6 composite material, in which the carbon fiber content was 20 wt%, the PA6 content was 65 wt%, and the SEBS-g-MAH content was 15 wt%. The crystallization temperature of the composite material was tested by differential scanning calorimetry (DSC).
[0085] 2. The carbon fiber reinforced PA6 composite material was printed into a standard mechanical spline using the FDM process. The nozzle size was 0.4 mm, the nozzle temperature was 240 °C, the printing speed was 60 mm / s, and the printing direction was the x-axis direction; the standard mechanical spline used to evaluate the interlayer bonding strength was printed in the z-axis direction. The tensile strength of the spline was tested using an electronic tensile machine, and the notched impact strength of the spline was tested using an impact tester.
[0086] Embodiment 6:
[0087] 1. The re-sized carbon fiber tow was pulled into a twin-screw extruder, melt-mixed with PA6 and SEBS-g-MAH, and granulated to obtain a carbon fiber reinforced PA6 composite material, wherein the carbon fiber content was 20 wt%, the PA6 content was 50 wt%, and the SEBS-g-MAH content was 30 wt%. The crystallization temperature of the composite material was tested by differential scanning calorimetry (DSC).
[0088] 2. The carbon fiber reinforced PA6 composite material was printed into a standard mechanical spline using the FDM process. The nozzle size was 0.4 mm, the nozzle temperature was 240 °C, the printing speed was 60 mm / s, and the printing direction was the x-axis direction; the standard mechanical spline used to evaluate the interlayer bonding strength was printed in the z-axis direction. The tensile strength of the spline was tested using an electronic tensile machine, and the notched impact strength of the spline was tested using an impact tester.
[0089] The present invention additionally provides six comparative examples, which are:
[0090] Comparative Example 1:
[0091] The only difference from Example 1 is that commercially available epoxy sizing agent carbon fiber tow is used.
[0092] Comparative Example 2:
[0093] The only difference from Example 2 is that commercially available epoxy sizing agent carbon fiber tow is used.
[0094] Comparative Example 3:
[0095] The only difference from Example 3 is that commercially available epoxy sizing agent carbon fiber tow is used.
[0096] Comparative Example 4:
[0097] The only difference from Example 4 is that the toughening phase used is SEBS.
[0098] Comparative Example 5:
[0099] The only difference from Example 5 is that the toughening phase used is SEBS.
[0100] Comparative Example 6:
[0101] The only difference from Example 6 is that the toughening phase used is SEBS.
[0102] For the convenience of comparison, the re-sized carbon fiber tows prepared by the preferred process were uniformly used in the examples for the experiments; the extrusion mixing temperature was also uniformly 255° C. The test results of mechanical properties and crystallization behavior are shown in Table 1.
[0103] Table 1 Tensile strength data of fused deposition modeling products prepared in Examples 1-6 and Comparative Examples 1-6
[0104] Case X-direction tensile strength Notched impact strength Z-direction tensile strength Crystallization temperature Example 1 89±1.9 MPa <![CDATA[36±1.6 kJ / m 2 ]]> 55±3.3 MPa 176.6 ℃ Example 2 133±2.6 MPa <![CDATA[35±1.4 kJ / m 2 ]]> 59±2.7 MPa 174.1 ℃ Example 3 139±3.1 MPa <![CDATA[24±1.9 kJ / m 2 ]]> 45±4.4 MPa 174.7 ℃ Example 4 157±3.8 MPa <![CDATA[7.2±2.0 kJ / m 2 ]]> 33±2.2 MPa 181.0 ℃ Example 5 143±4.5 MPa <![CDATA[21±2.4 kJ / m 2 ]]> 37±3.2 MPa 179.3 ℃ Example 6 78±4.9 MPa <![CDATA[33±1.5 kJ / m 2 ]]> 19±1.9 MPa 173.3 ℃ Comparative Example 1 56±2.0 MPa <![CDATA[30±1.8 kJ / m 2 ]]> 17±1.3 MPa 176.9 ℃ Comparative Example 2 63±2.7 MPa <![CDATA[28±1.6 kJ / m 2 ]]> 14±1.3 MPa 176.3 ℃ Comparative Example 3 68±3.3 MPa <![CDATA[23±2.5 kJ / m 2 ]]> 12±1.8 MPa 176.0 ℃ Comparative Example 4 118±0.9 MPa <![CDATA[6.7±2.1 kJ / m 2 ]]> 22±1.3 MPa 183.1 ℃ Comparative Example 5 112±1.6 MPa <![CDATA[6.9±1.1 kJ / m 2 ]]> 19±3.7 MPa 182.6 ℃ Comparative Example 6 97±2.2 MPa <![CDATA[14±1.4 kJ / m 2 ]]> 18±4.1 MPa 179.2 ℃
[0105] As shown in Table 1, the carbon fiber reinforced PA6 composite material prepared by the present invention can show excellent tensile strength and impact strength for 3D printing, and the tensile strength in the z direction is also significantly higher, indicating that the interlayer bonding strength of the workpiece is improved. The improvement of the tensile strength in the x direction is mainly due to the enhanced interface effect between the re-sized carbon fiber and the PA6 matrix; the improvement of the impact strength is mainly due to the strong interface effect formed by the reaction of maleic anhydride on the SEBS-g-MAH molecular chain and the amino group on the PA6 molecular chain; the improvement of the interlayer bonding strength is on the one hand that the addition of SEBS-g-MAH reduces the crystallization temperature of PA6, and on the other hand, the strong interaction between SEBS-g-MAH and the PA6 molecular chain is formed at the interlayer interface.
[0106] like Figure 2 As shown, Figure 2 Figures a and b are SEM micrographs of the brittle fracture surfaces of the carbon fiber reinforced PA6 composite materials in Example 2 and Comparative Example 2, respectively. As can be seen from the figure, the re-sized carbon fibers in Example 2 have a good interface bond with the PA6 matrix, and most of the carbon fibers are well coated by the PA6 matrix; while the carbon fibers with epoxy sizing agent in Comparative Example 2 have a weak bond with the PA6 matrix, and most of the carbon fibers are exposed outside the PA6 matrix.
[0107] like Figure 3 As shown, Figure 3 4 and 5 are DSC curves of the carbon fiber reinforced PA6 composite materials in Example 4, Comparative Example 4, Example 5 and Comparative Example 5. It can be seen from the figure that increasing the content of SEBS or SEBS-g-MAH helps to reduce the crystallization temperature of PA6; and the effect of SEBS-g-MAH is more significant than that of SEBS.
[0108] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0109] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A carbon fiber reinforced PA6 composite material for 3D printing, characterized in that: The composite material is composed of the following components in percentage by weight: PA6: 50wt%-95wt%; Carbon fiber: 1wt%-45wt%; SEBS: 3wt%-30wt%.
2. The composite material according to claim 1, characterized in that The SEBS is at least one of unmodified SEBS and SEBS-g-MAH.
3. A method for preparing a carbon fiber reinforced PA6 composite material for 3D printing, characterized in that: include: Modify the surface of carbon fiber; The modified carbon fiber tow is pulled into a twin-screw extruder for melt mixing and granulation with PA6 and SEBS to obtain a carbon fiber reinforced PA6 composite material.
4. The method according to claim 3, characterized in that Based on the carbon fiber reinforced PA6 composite material for 3D printing, the surface of the carbon fiber is modified as follows: Desizing the carbon fiber tow; alkaline treating the desized carbon fiber tow; treating the desized carbon fiber tow after the alkali treatment with silane; Grafting maleic anhydride onto a silane-treated desized carbon fiber tow; The grafted desized carbon fiber tow is re-sized.
5. The method according to claim 4, characterized in that The carbon fiber tow is desizing treated as follows: The desizing is completed by pulling the carbon fiber tow through a high temperature furnace, wherein the temperature is 200-400°C and the time of passing through the high temperature furnace is 0.5-3 minutes.
6. The method according to claim 5, characterized in that The desized carbon fiber tow is subjected to alkali treatment, specifically: The desized carbon fiber tow is driven by traction to pass through a sodium hydroxide aqueous solution, wherein the concentration of the sodium hydroxide aqueous solution is 10 mol / L, and the passing time is 0.5-3 minutes. After passing through, the tow enters a clean water tank for cleaning.
7. The method according to claim 6, characterized in that The desized carbon fiber tow after alkali treatment is subjected to silane treatment, specifically: The cleaned desized carbon fiber tow is driven by traction to pass through a silane solution, wherein the silane is at least one of trimethoxysilane and triethoxysilane, the solvent of the silane solution is a mixed solution including water and ethanol or methanol, the volume ratio of water / ethanol or methanol is 90 / 10-20 / 80, the silane content in the silane solution is 0.5 wt%-20 wt%, and the time for passing through the silane solution is 5-30 minutes.
8. The method according to claim 7, characterized in that The desized carbon fiber tow treated with silane is grafted with maleic anhydride, specifically: The desized carbon fiber tow treated with silane is driven by pulling through an aqueous maleic anhydride solution, wherein the maleic anhydride content is 1 wt%-30 wt%, the Custer catalyst content in the aqueous maleic anhydride solution is 0.1 wt%, the temperature of the aqueous maleic anhydride solution is 40-80°C, and the time of passing through the aqueous maleic anhydride solution is 5-30 minutes.
9. The method according to claim 8, characterized in that The grafted desized carbon fiber tow is re-sized, specifically: The grafted desized carbon fiber tow is driven by traction and dried in a blast high-temperature furnace, wherein the temperature is 120-180°C and the passing time is 2 minutes. The dried desized carbon fiber filaments are impregnated in a low molecular weight PA6 melt, wherein the PA6 molecular weight is 1000-11000 g / mol, the low molecular weight PA6 melt temperature is 220-260°C, and the passing time is 1-5 minutes, thereby completing the re-sizing.
10. The method according to claim 9, characterized in that The modified carbon fiber tow is pulled into a twin-screw extruder for melt mixing and granulation with PA6 and SEBS to obtain a carbon fiber reinforced PA6 composite material, specifically: The re-sized carbon fiber tow is pulled into a twin-screw extruder for melt mixing and granulation with PA6 and SEBS to obtain a carbon fiber reinforced PA6 composite material, wherein the molecular weight of PA6 is 12000-57000 g / mol and the extrusion mixing temperature is 220-270 °C.
Citation Information
Patent Citations
Waste carbon fiber reinforced nylon 6 composite material and preparation method thereof
CN102181150A
Carbon fiber-reinforced nylon 6 composite material with high flowability and good surface and preparation method thereof
CN106589920A
High performance long carbon fiber enhanced nylon composite material and preparation method thereof
CN110256846A
Carbon fiber reinforced polyamide composite material product and preparation method thereof
CN110423462A
Carbon fiber sizing agent as well as preparation method and application thereof
CN117887085A
